Greetings from witness protection! - Burt, Jake (Square Fish, 2018)
Nicki's life has been anything but easy. She's been in and out of foster homes and always finds her way back to the center with the other orphans. So when a marshal sets her up with a family living in the witness protection program as a means of fooling any criminals on their trail looking for a family of three instead of a family of four, she looks forward to the challenge. But maintaining a B-minus average while keeping her new family safe from hitmen is harder than she imagined--especially when her own past comes back to haunt her.